1847 Pa. Laws 266 - (:unkn) unknown (My University, 1847)
No. 208, § 1: That if any person shall open any tomb or grave in the lands of the cemetery of Laurel Hill cemetery company of Philadelphia . . . or shall shoot or discharge any gun or other fire arms within said limits shall be deemed guilty of a misdemeanor. . .
Keywords: DISCHARGE